2008
DOI: 10.1002/mats.200700063
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Crystallization: A DSC Approach to Building the T‐CR‐T Diagram

Abstract: T‐CR‐T diagrams are one of the most reliable ways to predict the thermal behavior of material solidification from the melt. A brief description of solidification accounting for continuous cooling is presented for fast‐crystallizing polymers. An isoconversional method is applied to the kinetic analysis of non‐isothermal processes. The solidification process of different polymer materials: high density polyethylene based samples and mixtures of PEG with a pharmaceutical drug were analyzed by means of DSC. Severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Table 2 shows the thermal and crystallization properties parameters of pure PCL and PCL/CS whisker composites determined by DSC measurement. The undercooling $T in Table 2 is defined using Equation (1) [27]:…”
Section: Results and Discussion 31 Morphology Of Fracture Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 shows the thermal and crystallization properties parameters of pure PCL and PCL/CS whisker composites determined by DSC measurement. The undercooling $T in Table 2 is defined using Equation (1) [27]:…”
Section: Results and Discussion 31 Morphology Of Fracture Surfacesmentioning
confidence: 99%
“…The difference in impact strength between the composites prepared by two methods should be ascribed to several factors such as spherulite size, whisker debonding during impact test and whisker length. It is reported that the decrease of spherulite size will benefit the improvement of impact strength [27]. POM observation shows that the composites prepared by coprecipitation have smaller spherulite size.…”
Section: Mechanical Propertiesmentioning
confidence: 95%
“…The undercooling shown in Table 1 is defined as the difference between melting and crystallization temperatures [21]: where T m and T c are the melting and crystallization temperatures determined from Figs. 3–6, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, experimental values of B α appear to show reasonable constancy [36,96]. Most importantly, both techniques allow one to simulate the time-cooling rate-transformation and TTT diagrams [36,[94][95][96]. Similar evaluations can be carried out by using the method of Dobreva et al [97,98].…”
Section: Turnbull-fisher Treatment For Broad Temperature Rangementioning
confidence: 95%
“…An advantage of such a method is that one can also test the constancy of B α , which is expected based on Equation (23). Indeed, experimental values of B α appear to show reasonable constancy [36,96]. Most importantly, both techniques allow one to simulate the time-cooling rate-transformation and TTT diagrams [36,[94][95][96].…”
Section: Turnbull-fisher Treatment For Broad Temperature Rangementioning
confidence: 99%